Molecular Cloning and Function Analysis of Two SQUAMOSA‐Like MADS‐Box Genes From Gossypium hirsutum L.1. Issue 7 (18th July 2013) - Zhang, Wenxiang; Fan, Shuli; Pang, Chaoyou; Wei, Hengling; Ma, Jianhui; Song, Meizhen; Yu, Shuxun
Abstract: The MADS‐box genes encode a large family of transcription factors having diverse roles in plant development. The SQUAMOSA (SQUA)/APETALA1 (AP1)/FRUITFULL (FUL) subfamily genes are essential regulators of floral transition and floral organ identity. Here we cloned two MADS‐box genes, GhMADS22 and GhMADS23, belonging to the SQUA/AP1/FUL subgroup from Gossypium hirsutum L. Phylogenetic analysis and sequence alignment showed that GhMADS22 and GhMADS23 belonged to the euFUL and euAP1 subclades, respectively. The two genes both had eight exons and seven introns from the start codon to the stop codon according to the alignment between the obtained cDNA sequence and the Gossypium raimondii L. genome sequence. Expression profile analysis showed that GhMADS22 and GhMADS23 were highly expressed in developing shoot apices, bracts, and sepals. Gibberellic acid promoted GhMADS22 and GhMADS23 expression in the shoot apex. Transgenic Arabidopsis lines overexpressing 35S:: GhMADS22 had abnormal flowers and bolted earlier than wild type under long‐day conditions (16 h light/8 h dark). Moreover, GhMADS22 overexpression delayed floral organ senescence and abscission and it could also respond to abscisic acid. In summary, GhMADS22 may have functions in promoting flowering, improving resistance and delaying senescence for cotton and thus it may be a candidate target for promoting early‐maturation in cotton breeding.